Energy efficiency optimization method for multi-user simultaneous wireless information and power transfer - Chao CHEN; Cheng PENG; Shengli ZHOU; Bo PAN (Dianxin kexue)
Joint transceiver design for achieving energy efficiency maximization was studied in multi-user downlink systems with simultaneous wireless information and power transfer. An improved Dinkelbach method was proposed. Specifically, the problem is converted to a series of subtraction form problems following the basic idea of Dinkelbach method. By introducing a set of auxiliary variables, the subtraction form problem is further equivalently cast as a weighted mean-square-error minimization problem, which is solved by using concave-convex procedure and second-order-cone programming（SOCP）. Simulation results validates the efficiency of the proposed method.